Working Woman Orientations for Fixing the Ideal Number of Family Members – A field study applied on sample of women working in Riyadh city – - Almadani, Suoad Abdulaziz (Journal of Humanities & Social Sciences, 2021)
This study is considered one of the descriptive studies that seeks to identify the attitudes of working women towards determining the optimal size of the family. It also uses the social survey method in the sampling method, through the use of a random sample for a group of female employees in a number of schools affiliated with the Supervision Office in the south of Riyadh. The sample size was 152 female employees from all schools. The researcher used a tool (questionnaire) to collect data as a tool consistent with the nature of the method used. From the results of the study, it was found that the average optimal number for both males and females is (3) children. It was also found that there is some agreement among the study sample on the social and economic factors affecting the size of the family.